Evaluation and applications of quantum algorithms - Chong, Chris Yong Jian (Nanyang Technological University, 2023)
Quantum computing is an exciting field of computing that harnesses the principles of quantum mechanics to perform certain type of calculations much faster than classical computers. This includes tasks like factoring large numbers, searching unsorted databases, simulating quantum systems and optimising complex systems. Quantum computing has the potential to disrupt various industries by accelerating problem-solving and innovation.